High-sheet-resistance silicon solar cell front silver electrode slurry
By adding nano-scale silver particles and other components with specific ratios to the silver electrode paste on the front of the solar cell, a conductive network is formed, which solves the problem of insufficient conductivity of traditional silver paste and achieves efficient and stable improvement of solar cell performance.
Patent Information
- Application Number
- CN202411645428.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The silver paste on the front of traditional solar cells has problems such as insufficient conductivity, high square resistance and expensive production costs.
A high square resistance silicon solar cell front silver electrode paste is used, including nano-scale silver particles, polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, nanoparticles such as copper and platinum, polyaniline, Components such as polythiophene, ethyl acetate, dimethylformamide, toluene, ethylene glycol and deionized water form a conductive network through specific ratios and process steps to improve the conductivity of the electrode.
This slurry can improve the efficiency and performance of solar cells, enhance the conductivity and stability of electrodes, reduce production costs, and improve the conversion efficiency and long-term stability of solar cells.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar energy paste, in particular to a front silver electrode paste for a high square resistance silicon solar cell. Background Art
[0002] Solar cells are devices that convert light energy into electrical energy through the photoelectric effect. Radiation of a suitable wavelength incident on the PN junction of a semiconductor acts as an external energy source to generate hole-electron pairs in the semiconductor. Due to the potential difference at the PN junction, holes and electrons move across the junction in opposite directions. Electrons move to the negative electrode contact and holes move to the positive electrode contact, thereby generating a current that can deliver power to the external circuit. The electrode contacts of solar cells are important for the performance of the cell. The front electrode paste of solar cells is an important basic material for making photovoltaic solar cells and is used to make the front electrode of crystalline silicon solar cells. The front electrode of solar cells is composed of glass powder, silver powder, organic carrier, inorganic additives, and organic additives; the main function of glass powder is to burn through the insulating silicon nitride anti-reflection film, help form Ag / Si ohmic contact, and provide adhesion; the main function of silver powder is to sinter and densify the silver powder, form a low grid line resistance, and provide a good conductive electrode; the main function of the organic carrier is the wetting, printability, appearance, and aspect ratio between powders; inorganic additives and organic additives are mainly used for modification and improvement of paste performance.
[0003] Silver paste is often used as a conductive layer in the front electrode of current solar cells to achieve current transmission. However, traditional silver paste has insufficient conductivity, high square resistance, and high production cost. Here we propose a high square resistance silicon solar cell front silver electrode paste. Summary of the invention
[0004] The present invention solves the above technical deficiencies and adopts a modified technical solution. A high square resistivity silicon solar cell front silver electrode slurry comprises the following raw materials and their weight proportions: 4-10 parts of nanometer-scale silver particles, 1-2 parts of polyvinyl alcohol, 2.5-5 parts of polystyrene, 2-4 parts of acrylate copolymer, 1.5-3 parts of carboxymethyl cellulose, 3-6 parts of nanometer particles such as copper, 1-2 parts of nanometer particles such as platinum, 2-4 parts of polyaniline, 0.5-2 parts of polythiophene, 2-5 parts of ethyl acetate, 1-3 parts of dimethylformamide, 2.5-5 parts of toluene, 3-8 parts of ethylene glycol and 6-14 parts of deionized water.
[0005] As a further preferred embodiment of the present invention, the following raw materials and their weight proportions are also included, including 10 parts of nanoscale silver particles, 2 parts of polyvinyl alcohol, 5 parts of polystyrene, 4 parts of acrylate copolymer, 3 parts of carboxymethyl cellulose, 6 parts of nanoparticles such as copper, 2 parts of nanoparticles such as platinum, 4 parts of polyaniline, 2 parts of polythiophene, 5 parts of ethyl acetate, 3 parts of dimethylformamide, 5 parts of toluene, 8 parts of ethylene glycol, and 14 parts of deionized water.
[0006] As a further preferred embodiment of the present invention, the following raw materials and their weight proportions are also included, including 4 parts of nanoscale silver particles, 1 part of polyvinyl alcohol, 2.5 parts of polystyrene, 2 parts of acrylate copolymer, 1.5 parts of carboxymethyl cellulose, 3 parts of nanoparticles such as copper, 1 part of nanoparticles such as platinum, 2 parts of polyaniline, 0.5 parts of polythiophene, 2 parts of ethyl acetate, 1 part of dimethylformamide, 2.5 parts of toluene, 3 parts of ethylene glycol, and 6 parts of deionized water.
[0007] As a further preferred embodiment of the present invention, the manufacturing process steps are as follows:
[0008] S1, first, add half amount of deionized water into a clean container and stir evenly to form a basic solution, then add polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, polyaniline and polythiophene into the basic solution respectively, stir and mix, evenly disperse them in a stirring container for circulated stirring, and then fully immerse for 0.5-2 hours, and control the temperature to reach 72°C;
[0009] S2, gradually adding nanoparticles such as copper and nanoparticles such as platinum to the solution, continuing to stir and mix, ensuring that the nanoparticles are evenly dispersed in the solution, adding nanoscale silver particles, gradually adding and stirring and mixing, ensuring that the silver particles are evenly dispersed in the solution and form a conductive network, and adding half the amount of deionized water;
[0010] S3, mixing and stirring the above solutions, then heating to 80-95° C., stirring for 30-45 minutes, gradually adding organic solvents such as ethyl acetate, dimethylformamide and toluene to adjust the viscosity and fluidity of the solution, and continuing to stir and mix until the solution reaches coating performance;
[0011] S4, adding ethylene glycol, continuing to stir and mix to increase the viscosity and stability of the solution, stirring the slurry evenly, and using ultrasonic treatment to eliminate potential bubbles and agglomerates.
[0012] As a further preferred embodiment of the present invention, the average diameter of the nano-scale silver particles is 4-80 nanometers, and the average diameter of the nanoparticles such as copper and nanoparticles such as platinum is 10-100 nanometers.
[0013] As a further preferred embodiment of the present invention, in step S2, after adding deionized water, the mixture is stirred at a speed of 430-550 r / min for 20-30 minutes before cooling down, and the standing time is continued for 1-2 hours, and the temperature is controlled between 60-85°C.
[0014] As a further preferred embodiment of the present invention, in step S4, the ultrasonic treatment is performed at a power between 10 and 100 watts, a frequency range of 30 kHz to 200 kHz, a time controlled between 25 and 45 minutes, and a temperature controlled between 30 and 45°C.
[0015] The beneficial effects achieved by the present invention are as follows: the slurry can be used to prepare the front silver electrode of high square resistance silicon solar cells, and the electrode can improve the efficiency and performance of solar cells; the nano-scale silver particles, nano-particles such as copper and nano-particles such as platinum in the slurry can form a conductive network to improve the conductive performance of the electrode; the viscosity, fluidity and stability of the slurry can be adjusted by controlling the composition of the slurry and the parameters in the preparation process, so that it is suitable for coating on solar cells; the use of ultrasonic treatment can eliminate bubbles and agglomerates in the slurry, further improve the uniformity and quality of the slurry, and effectively improve the performance of the front silver electrode of the high square resistance silicon solar cell as a whole, improve the conversion efficiency of the solar cell, and enhance its long-term stability and reliability. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The present invention provides a technical solution: a high square resistance silicon solar cell front silver electrode slurry, comprising the following raw materials and weight proportions: 4-10 parts of nanometer-scale silver particles, 1-2 parts of polyvinyl alcohol, 2.5-5 parts of polystyrene, 2-4 parts of acrylate copolymer, 1.5-3 parts of carboxymethyl cellulose, 3-6 parts of nanometer particles such as copper, 1-2 parts of nanometer particles such as platinum, 2-4 parts of polyaniline, 0.5-2 parts of polythiophene, 2-5 parts of ethyl acetate, 1-3 parts of dimethylformamide, 2.5-5 parts of toluene, 3-8 parts of ethylene glycol, and 6-14 parts of deionized water. Carbon nanotubes:
[0018] Carbon nanotubes are a type of nanomaterial with excellent electrical conductivity. Adding carbon nanotubes to silver paste can form a three-dimensional conductive network, improve the electrical conductivity of the silver paste, and effectively enhance the efficiency of electron transfer.
[0019] Metal Nanoparticles:
[0020] In addition to silver particles, other metal nanoparticles such as copper and platinum can also be used as conductive additives. These metal nanoparticles have excellent conductive properties and can form conductive channels with silver particles to improve the overall conductive properties of the silver paste.
[0021] Conductive polymers:
[0022] Conductive polymers, such as polyaniline and polythiophene, can be added to silver paste as conductive additives. These conductive polymers have good conductivity and can form conductive paths to improve the conductivity and electron transport capacity of silver paste.
[0023] The invention also includes the following raw materials and their weight proportions, including 10 parts of nanometer-scale silver particles, 2 parts of polyvinyl alcohol, 5 parts of polystyrene, 4 parts of acrylate copolymer, 3 parts of carboxymethyl cellulose, 6 parts of nanometer particles such as copper, 2 parts of nanometer particles such as platinum, 4 parts of polyaniline, 2 parts of polythiophene, 5 parts of ethyl acetate, 3 parts of dimethylformamide, 5 parts of toluene, 8 parts of ethylene glycol, and 14 parts of deionized water.
[0024] Polyvinyl alcohol:
[0025] PVA is a commonly used organic polymer additive with good solubility and adhesion properties. It can increase the adhesion of silver paste, ensure the good adhesion of silver particles on the electrode surface, and has high light transmittance without significant impact on optical properties.
[0026] Polystyrene:
[0027] PS is an organic polymer with excellent optical properties. Adding an appropriate amount of PS to the silver paste can increase the optical absorption capacity of the paste and improve the light absorption efficiency of solar cells. In addition, PS can also improve the adhesion of the silver paste and enhance the bonding force with the electrode surface.
[0028] Acrylate Copolymer:
[0029] Acrylate copolymers are a type of commonly used organic polymer additives that have good adhesion, flexibility and optical transparency. Adding acrylate copolymers to silver paste can improve the adhesion of the paste, making it more firmly attached to the substrate, and has better light transmittance without causing significant optical loss.
[0030] Carboxymethyl cellulose:
[0031] CMC is a water-soluble organic polymer with good adhesion and rheological properties. Adding CMC to silver paste can increase the adhesion of the paste, making it better adhere to the substrate, and can adjust the viscosity of the paste, improve its fluidity, and facilitate processing and coating.
[0032] The invention also includes the following raw materials and their weight proportions, including 4 parts of nanometer-scale silver particles, 1 part of polyvinyl alcohol, 2.5 parts of polystyrene, 2 parts of acrylate copolymer, 1.5 parts of carboxymethyl cellulose, 3 parts of nanometer particles such as copper, 1 part of nanometer particles such as platinum, 2 parts of polyaniline, 0.5 parts of polythiophene, 2 parts of ethyl acetate, 1 part of dimethylformamide, 2.5 parts of toluene, 3 parts of ethylene glycol, and 6 parts of deionized water.
[0033] The production process steps are as follows:
[0034] S1, first, add half amount of deionized water into a clean container and stir evenly to form a basic solution, then add polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, polyaniline and polythiophene into the basic solution respectively, stir and mix, evenly disperse them in a stirring container for circulated stirring, and then fully immerse for 0.5-2 hours, and control the temperature to reach 72°C;
[0035] S2, gradually adding nanoparticles such as copper and nanoparticles such as platinum to the solution, continuing to stir and mix, ensuring that the nanoparticles are evenly dispersed in the solution, adding nanoscale silver particles, gradually adding and stirring and mixing, ensuring that the silver particles are evenly dispersed in the solution and form a conductive network, and adding half the amount of deionized water;
[0036] S3, mixing and stirring the above solutions, then heating to 80-95° C., stirring for 30-45 minutes, gradually adding organic solvents such as ethyl acetate, dimethylformamide and toluene to adjust the viscosity and fluidity of the solution, and continuing to stir and mix until the solution reaches coating performance;
[0037] S4, adding ethylene glycol, continuing to stir and mix to increase the viscosity and stability of the solution, stirring the slurry evenly, and using ultrasonic treatment to eliminate potential bubbles and agglomerates.
[0038] The average diameter of the nanometer-scale silver particles is 4-80 nanometers, and the average diameter of the nanometer particles such as copper and nanometer particles such as platinum is 10-100 nanometers.
[0039] In step S2, after adding deionized water, stir at a speed of 430-550 r / min for 20-30 minutes and then cool down. The standing time is 1-2 hours and the temperature is controlled between 60-85°C.
[0040] In step S4, ultrasonic treatment is performed at a power between 10 and 100 watts, a frequency range of 30 kHz to 200 kHz, a time controllable between 25 and 45 minutes, and a temperature controllable between 30 and 45°C.
[0041] Example 1
[0042] A high square resistance silicon solar cell front silver electrode slurry comprises 10 parts of nanometer-level silver particles, 2 parts of polyvinyl alcohol, 5 parts of polystyrene, 4 parts of acrylate copolymer, 3 parts of carboxymethyl cellulose, 6 parts of nanometer particles such as copper, 2 parts of nanometer particles such as platinum, 4 parts of polyaniline, 2 parts of polythiophene, 5 parts of ethyl acetate, 3 parts of dimethylformamide, 5 parts of toluene, 8 parts of ethylene glycol and 14 parts of deionized water.
[0043] The production process steps are as follows:
[0044] First, add half amount of deionized water into a clean container and stir evenly to form a basic solution. Then, add polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, polyaniline and polythiophene into the basic solution respectively, stir and mix, and evenly disperse them in a stirring container for circulated stirring. Then, fully immerse them for 2 hours and control the temperature to 72°C.
[0045] Nanoparticles such as copper and nanoparticles such as platinum are gradually added to the solution, and stirring and mixing are continued to ensure that the nanoparticles are evenly dispersed in the solution. Nano-scale silver particles are added, and gradually added and stirred to ensure that the silver particles are evenly dispersed in the solution and form a conductive network. Half amount of deionized water is added. After adding deionized water, the speed is 550r / min, stirred for 30 minutes, and then the temperature is lowered. The standing time is continued for 1-2h, and the temperature is controlled between 85°C;
[0046] The above solutions were mixed and stirred, and then heated to 95°C. After stirring for 45 minutes, organic solvents such as ethyl acetate, dimethylformamide and toluene were gradually added to adjust the viscosity and fluidity of the solution. The solution was stirred and mixed continuously until the solution reached coating performance.
[0047] Add ethylene glycol and continue to stir and mix to increase the viscosity and stability of the solution. Stir the slurry evenly and use ultrasonic treatment to eliminate potential bubbles and agglomerates. The ultrasonic treatment is between 100 watts, the frequency range is 200 kHz, the time is controlled between 45 minutes, and the temperature is controlled between 45°C.
[0048] The average size of nanometer-scale silver particles is 80 nanometers, and the average size of nanometer-scale particles such as copper and nanometer-scale particles such as platinum is 100 nanometers.
[0049] Example 2
[0050] A high square resistance silicon solar cell front silver electrode slurry comprises 10 parts of nanometer-level silver particles, 2 parts of polyvinyl alcohol, 5 parts of polystyrene, 4 parts of acrylate copolymer, 3 parts of carboxymethyl cellulose, 6 parts of nanometer particles such as copper, 2 parts of nanometer particles such as platinum, 4 parts of polyaniline, 2 parts of polythiophene, 5 parts of ethyl acetate, 3 parts of dimethylformamide, 5 parts of toluene, 8 parts of ethylene glycol and 14 parts of deionized water.
[0051] The production process steps are as follows:
[0052] First, add half amount of deionized water into a clean container and stir evenly to form a basic solution. Then, add polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, polyaniline and polythiophene into the basic solution respectively, stir and mix, and evenly disperse them in a stirring container for circulated stirring. Then, fully immerse them for 0.5 hours and control the temperature to 72°C.
[0053] Nanoparticles such as copper and nanoparticles such as platinum are gradually added to the solution, and stirring and mixing are continued to ensure that the nanoparticles are evenly dispersed in the solution. Nano-sized silver particles are added, and gradually added and stirred to ensure that the silver particles are evenly dispersed in the solution and form a conductive network. Half amount of deionized water is added. After adding deionized water, the speed is 430r / min, stirred for 20 minutes, and then the temperature is lowered. The standing time is continued for 1 hour, and the temperature is controlled between 60°C;
[0054] The above solutions were mixed and stirred, and then heated to 80°C. After stirring for 30 minutes, organic solvents such as ethyl acetate, dimethylformamide and toluene were gradually added to adjust the viscosity and fluidity of the solution. The solution was stirred and mixed continuously until the solution reached coating performance.
[0055] Add ethylene glycol and continue to stir and mix to increase the viscosity and stability of the solution. Stir the slurry evenly and use ultrasonic treatment to eliminate potential bubbles and agglomerates. The ultrasonic treatment is between 10 watts, the frequency range is 30 kHz, the time is controlled between 25-45 minutes, and the temperature is controlled between 30°C. The average size of the nano-scale silver particles is 4 nanometers, and the average size of the nano-particles such as copper and nano-particles such as platinum is 10 nanometers.
[0056] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0057] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high square resistance silicon solar cell front silver electrode paste, characterized in that: The invention comprises the following raw materials and their weight proportions: 4-10 parts of nanometer-scale silver particles, 1-2 parts of polyvinyl alcohol, 2.5-5 parts of polystyrene, 2-4 parts of acrylate copolymer, 1.5-3 parts of carboxymethyl cellulose, 3-6 parts of nanometer-scale particles such as copper, 1-2 parts of nanometer-scale particles such as platinum, 2-4 parts of polyaniline, 0.5-2 parts of polythiophene, 2-5 parts of ethyl acetate, 1-3 parts of dimethylformamide, 2.5-5 parts of toluene, 3-8 parts of ethylene glycol and 6-14 parts of deionized water.
2. The high square resistance silicon solar cell front silver electrode slurry according to claim 1, characterized in that: The invention also includes the following raw materials and their weight proportions, including 10 parts of nanometer-scale silver particles, 2 parts of polyvinyl alcohol, 5 parts of polystyrene, 4 parts of acrylate copolymer, 3 parts of carboxymethyl cellulose, 6 parts of nanometer particles such as copper, 2 parts of nanometer particles such as platinum, 4 parts of polyaniline, 2 parts of polythiophene, 5 parts of ethyl acetate, 3 parts of dimethylformamide, 5 parts of toluene, 8 parts of ethylene glycol, and 14 parts of deionized water.
3. The high square resistance silicon solar cell front silver electrode slurry according to claim 1, characterized in that: The invention also includes the following raw materials and their weight proportions, including 4 parts of nanometer-scale silver particles, 1 part of polyvinyl alcohol, 2.5 parts of polystyrene, 2 parts of acrylate copolymer, 1.5 parts of carboxymethyl cellulose, 3 parts of nanometer particles such as copper, 1 part of nanometer particles such as platinum, 2 parts of polyaniline, 0.5 parts of polythiophene, 2 parts of ethyl acetate, 1 part of dimethylformamide, 2.5 parts of toluene, 3 parts of ethylene glycol, and 6 parts of deionized water.
4. The method for preparing a high square resistance silicon solar cell front silver electrode slurry according to claim 1, characterized in that: The production process steps are as follows: S1, first, add half amount of deionized water into a clean container and stir evenly to form a basic solution, then add polyvinyl alcohol, polystyrene, acrylate copolymer, carboxymethyl cellulose, polyaniline and polythiophene into the basic solution respectively, stir and mix, evenly disperse them in a stirring container for circulated stirring, and then fully immerse for 0.5-2 hours, and control the temperature to reach 72°C; S2, gradually adding nanoparticles such as copper and nanoparticles such as platinum to the solution, continuing to stir and mix, ensuring that the nanoparticles are evenly dispersed in the solution, adding nanoscale silver particles, gradually adding and stirring and mixing, ensuring that the silver particles are evenly dispersed in the solution and form a conductive network, and adding half the amount of deionized water; S3, mixing and stirring the above solutions, then heating to 80-95° C., stirring for 30-45 minutes, gradually adding organic solvents such as ethyl acetate, dimethylformamide and toluene to adjust the viscosity and fluidity of the solution, and continuing to stir and mix until the solution reaches coating performance; S4, adding ethylene glycol, continuing to stir and mix to increase the viscosity and stability of the solution, stirring the slurry evenly, and using ultrasonic treatment to eliminate potential bubbles and agglomerates.
5. The method for preparing a high square resistance silicon solar cell front silver electrode slurry according to claim 1, characterized in that: The average diameter of the nanometer-scale silver particles is 4-80 nanometers, and the average diameter of the nanometer particles such as copper and nanometer particles such as platinum is 10-100 nanometers.
6. The method for preparing a high square resistance silicon solar cell front silver electrode slurry according to claim 4, characterized in that: In step S2, after adding deionized water, stir at a speed of 430-550 r / min for 20-30 minutes and then cool down. The standing time is 1-2 hours and the temperature is controlled between 60-85°C.
7. The method for preparing a high square resistance silicon solar cell front silver electrode slurry according to claim 4, characterized in that: In step S4, ultrasonic treatment is performed at a power between 10 and 100 watts, a frequency range of 30 kHz to 200 kHz, a time controllable between 25 and 45 minutes, and a temperature controllable between 30 and 45°C.